Posterior thigh compartment syndrome associated with hamstring avulsion and antiplatelet therapy - Primavera, Matteo; Gatti, Andrea; Tarantino, Umberto; Gasparini, Monica (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of work: Posterior thigh compartment syndrome is a rare injury. We reported a case of a 49-year-old man developing posterior thigh compartment syndrome after an accidental fall at home causing hamstring tendon avulsion while assuming antiaggregant therapy. Methods: We decided to treat the patient with an immediate fasciotomy and tendon avulsion fixation with two anchors. Results: we managed to treat successfully our patient. Conclusions: We suggest to pay attention to a positive medical history for antiaggregant/anticoagulation therapy and to perform in the same surgical setting both fasciotomy and fixation.